2014
DOI: 10.1007/s00265-014-1761-4
|View full text |Cite
|
Sign up to set email alerts
|

Different tactics, one goal: initial reproductive investments of males and females in a small Arctic seabird

Abstract: Despite a great number of studies on extra-pair paternity in birds, the actual roles of males and females in extra-pair contacts is poorly understood, as detailed behavioural studies comparing the reproductive performance of the two sexes prior to egg laying are relatively scarce. Here, we investigated mating behaviour (copulations and aggressive interactions), time budget and body condition (size-adjusted body mass and baseline corticosterone level) in the little auk (Alle alle), a monogamous and highly colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…, Wojczulanis‐Jakubas et al . ). Thus, there is a potential risk of extra‐pair fertilization for males.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, Wojczulanis‐Jakubas et al . ). Thus, there is a potential risk of extra‐pair fertilization for males.…”
Section: Discussionmentioning
confidence: 97%
“…Whether male alcids guard their mates at sea to prevent extra-pair copulation is unclear. Extra-pair fertilization is not common in alcids (Anker-Nilssen et al 2010), as in other seabird families (Quillfeldt et al 2012), but extra-pair copulation has been observed often in alcids (Birkhead et al 1985, Wojczulanis-Jakubas et al 2014. Thus, there is a potential risk of extra-pair fertilization for males.…”
Section: Synchronized On-water/in-air Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high genetic homogeneity of the global population of the Little Auk (Wojczulanis‐Jakubas et al . ) and the fact that we performed the study in a single colony, we assumed homogeneous distribution of the traits within the study population (i.e. pooling of mating pairs from heterogeneous samples might potentially lead to ‘false–positive’ results, Fernández‐Meirama et al .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the idea that females control the success of copulations, we can expect that in long-lived species where males invest heavily in reproduction (e.g. colonial seabirds and raptors) they obviously tend to restrict EPCs, to avoid jeopardizing the male investment (Whittingham et al, 1992;Westneat and Sargent, 1996;Petrie and Kempenaers, 1998;Sheldon and Ellegren, 1998;Briggs and Collopy, 2012;Wojczulanis-Jakubas et al, 2014). In this regard, in raptors that nest in open country the fact that extra-pair interactions are visible or audible at long distances has also been suggested as a limiting factor in EPCs (Korpimäki et al, 1996).…”
Section: Extra-pair Copulationsmentioning
confidence: 99%